PWE-195 The enhanced recovery programme does not influence adjuvant chemotherapy rates following major pancreatic and liver resection surgery. (22nd June 2015) - Chan, A; Kotecha, S; Ali, Z; Lapsia, S; Krige, A; Coleman, H; Chang, D; Kausar, A; Harris, C; Subar, D
Abstract : Introduction: The Enhanced Recovery Programme (ERP) has been shown to improve postoperative complications and reduce hospital stay in patients undergoing major HPB surgical oncological resections. 1 The ERP should allow more patient autonomy in their care and extend beyond the current hospital admission. The benefits of the ERP following hospital discharge are unclear, particularly with regards to adjuvant chemotherapy completion rates. Method: A retrospective study was designed looking at the effect of the ERP on adjuvant chemotherapy rates following major pancreatic and liver resections. Patients deemed suitable for curative oncological resection surgery were included in the study. Neo-adjuvant and adjuvant chemotherapy regimens were decided as per the multidisciplinary team decision. Patients in the ERP group who didn't complete the ERP protocol were analysed in the EPR group on an intention-to-treat basis. Results: Between 2005 and 2013, 222 patients (100 liver resections and 122 pancreatic resections; median age 66 years, 1.4:1 male:female ratio) were identified and included in the study, with 142 patients (64.0%) following the ERP protocol. Two-thirds of patients in the ERP group successfully completed the ERP protocol. The ERP did not influence the time to chemotherapy (p = 0.14 pancreas group; p = 0.23 liver group) or successful completion of at least 6 cycles of chemotherapy (0.42 pancreas group; p = 0.06 liver group). Conclusion: The ERP has been shown to benefit patients in the immediate postoperative period, with a shorter hospital stay. The results of this study suggest that the benefit of the ERP following hospital discharge is limited and, in particular, does not affect the uptake or successful completion of adjuvant chemotherapy. The effect of the ERP on long-term outcome and cancer-specific survival is, however, still unclear. The ERP following major resection should be further developed to include a stronger community and primary care component to help facilitate care after discharge. Disclosure of interest: None Declared. Reference: . Jones C, Kelliher L, Dickinson M, et al . Randomized clinical trial on enhanced recovery versus standard care following open liver resection. Br J Surg. 2013July;100(8):1015–1024.